The Effect of Coffee Consumption Pattern on The Incidence of Dyspepsia in Medical Faculty Students - Habib Al Huda; Erlina Marfianti; Nurcholid Umam Kurniawan; Nuni Ihsana (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Dyspepsia syndrome can be defined as a collection of complaints described as pain or discomfort in the pit of the stomach, bloating, nausea, vomiting, belching, feeling full quickly, stomach feeling full or full. Based on the 2007 Indonesian Health Profile Information, dyspepsia was ranked 10th in the category of disease inpatients hospitalized in 2006 with 34,029 sufferers or approximately 1.59%. One of the various aspects of the risk of developing dyspepsia is consuming caffeine. Objective: This study aims to determine the influence of coffee consumption patterns on the incidence of dyspepsia in medical students of the Faculty of Medicine. Methods: This study uses an observational analytic method. The research was conducted in October 2021 – November 2021 at Medical Faculty, Ahmad Dahlan University. Research population was 110 active students of the 2018-2020 according to the inclusion and exclusion criteria. Analysis bivariate using chi-square. Results: It was found that the pattern of coffee consumption in students with the majority being in the moderate category was 87 people (79.1%) and the majority experienced the incidence of dyspepsia as many as 73 people (66.4%) while students with moderate consumption patterns had the greatest risk opportunity 1.753 times for experienced dyspepsia events with a relative risk ranging from 0.810 to 3.791. This shows the influence of coffee consumption patterns on the incidence of dyspepsia in students with a value of p = 0.002 (p <0.005). Conclusion: Coffee consumption patterns influence the incidence of dyspepsia in medical students, Medical Faculty Students, Ahmad Dahlan University.